2016
DOI: 10.1007/s11274-016-2112-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microbial communities during the anaerobic digestion of Gracilaria under mesophilic and thermophilic conditions

Abstract: Mesophilic and thermophilic anaerobic digesters (MD and TD, respectively) utilizing Gracilaria and marine sediment as the substrate and inoculum, respectively, were compared by analyzing their performances and microbial community changes. During three successive transfers, the average cumulative methane yields in the MD and TD were 222.6 ± 17.3 mL CH4/g volatile solids (VS) and 246.1 ± 11 mL CH4/g VS, respectively. The higher hydrolysis rate and acidogenesis in the TD resulted in a several fold greater accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…In R1 and R5, the methane and biogas yield were much lower than other rectors. In addition, the accumulation of acetate in R1 and R5 might result in the acidification in these reactors, which can deteriorate the anaerobic digestion process [36,37]. These physiochemical parameters of the reactors indicated that 1% RF concentration could not start the anaerobic digestion successfully, and 5% RF concentration could not achieve high methane production.…”
Section: Discussionmentioning
confidence: 99%
“…In R1 and R5, the methane and biogas yield were much lower than other rectors. In addition, the accumulation of acetate in R1 and R5 might result in the acidification in these reactors, which can deteriorate the anaerobic digestion process [36,37]. These physiochemical parameters of the reactors indicated that 1% RF concentration could not start the anaerobic digestion successfully, and 5% RF concentration could not achieve high methane production.…”
Section: Discussionmentioning
confidence: 99%
“…Purple nonsulfur bacteria are well-studied for their ability to grow under photoheterotrophic conditions using energy from light and various VFAs as carbon and electron sources. VFAs are common fermentation byproducts, and among them, acetate is usually one of the most abundant VFAs produced during the acidogenic and acetogenic phases of anaerobic digestion (3,4). Rs.…”
mentioning
confidence: 99%
“…Initial degradation of organic matter has been recorded to involve Proteobacteria, with many of them utilizing glucose and VFAs. Synergistetes have also been recorded to be related to the utilization of acetate …”
Section: Resultsmentioning
confidence: 99%
“…Synergistetes have also been recorded to be related to the utilization of acetate. [38][39][40] On day 10, the proportion of Bacteroidetes and Firmicutes in the intermittent reflux test (upper layer: 74.18%; lower layer: 52.1%) was generally higher than in the continuous reflux test (upper layer: 57.76%; lower layer: 47.34%). This selective enrichment might correlate with the improved cellulose degradation and it may account for the greater methane production in the intermittent reflux test.…”
Section: Wileyonlinelibrarycom/jctbmentioning
confidence: 99%